Malaria in Brazil: cases reported between 2010 and 2017 (Research, Society and Development, 2022)
Objective: To describe the number of reported cases of malaria in Brazil from 2010 to 2017. Method: This is a descriptive, retrospective and cross-sectional study. For the construction of the epidemiological database, the Malaria Epidemiological Surveillance Information System (SIVEP_Malaria) was used. This research is an analysis of secondary data, in which the research subjects were not approached, thus, there are no ethical implications because the analyzed data were obtained from a source in the public domain and there is no personal information of the individuals. Results: Of the twenty-six federative units in Brazil, twenty-two, including the Federal District, registered cases of malaria in the period from 2010 to 2017. In Brazil, it is noted that P.vivax is the most prevalent type of plasmodium. Conclusion: It is evident that Brazil, in the period studied (2010 to 2017), recorded a high number of cases of malaria. However, despite the high number, there was a reduction in cases following the global trend.